Pleomorphic xanthoastrocytoma: magnetic resonance imaging findings in a series of cases with histopathological confirmation Xantoastrocitoma pleomórfico: achados de ressonância magnética numa série de casos com confirmação histopatológica - Vinícius Trindade Gonçalves; Fabiano Reis; Luciano de Souza Queiroz; Marcondes França Jr (Arquivos de Neuro-Psiquiatria)
Pleomorphic xanthoastrocytoma (PXA) is a rare glioma. This paper aimed to analyze magnetic resonance imaging (MRI) characteristics in a series of patients diagnosed with PXA. We analyzed MRI findings in 9 patients with histopathologic diagnosis of PXA in our department over the last 12 years. The mean age of patients was 27.3 years. Cortical location was observed in all cases. The lesion imaging was solid-cystic in six cases. In eight cases, the solid component presented hypo or isointense on T1 and iso or hyperintense on T2. Contrast enhancement in the solid component was observed in eight cases. The observed imaging pattern of PXA was superficial location with leptomeningeal involvement, solid-cystic pattern and contrast enhancement in the solid component. We should consider that the association between PXA and other cortical tumors may occur, particularly, with gangliogliomas, which tend to be the main differential diagnosis in MRI. Xantoastrocitoma pleomórfico (PXA) é um glioma raro. Este estudo teve como objetivo analisar aspectos de imagem por ressonância magnética (RM) de uma série de pacientes com diagnóstico de PXA. Foram analisados exames de RM de 9 pacientes com diagnóstico histopatológico de PXA nos últimos 12 anos. A média de idade dos pacientes foi de 27,3 anos. Localização cortical foi observada em todos os casos. Padrão sólido-cístico foi observado em seis casos. Em oito casos, o componente sólido apresentou-se hipo ou isointenso em T1 e iso ou hiperintenso em T2. Foi observada captação de contraste na porção sólida em oito casos. O padrão de imagem observado do PXA foi de localização superficial com envolvimento leptomeníngeo, padrão sólido-cístico e captação de contraste pelo componente sólido. Devemos considerar que a associação entre PXA e outros tumores corticais pode ocorrer, particularmente, com ganglioglioma, que tende a ser o principal diagnóstico diferencial em RM.